Quantification of organic carbon and organic matter in soils with Avicennia germinans and Conocarpus erectus located in Boca de Uchire, Unare lagoon, Venezuela - Núñez-Ravelo, Franklin; Ugas-Pérez, María; Calderón-Castellanos, Rossany; Rivas-Meriño, Ferney (Revista Geográfica de América Central., 2021)
The purpose of the present study was to evidence the significant difference in the content of soil organic carbon (SOC) and soil organic matter (SOM) in three groups, namely: non-rhizospheric (nr), Avicennia germinans-covered (Ag) and Conocarpus erectus-covered (Ce). For this purpose, 54 surface soil samples (0-20 cm depth) were collected in the Boca de Uchire sector according to the following distribution: 18 nr, 18 Ag and 18 Ce. SOC content was determined by potassium dichromate wet-oxidation and percentage SOM calculated using the conventional van Bemmelen conversion factor (=1.724). Obtained data was treated by descriptive statistics analysis of ANOVA and Tukey’s test. The results show statistically significant differences among the three sample groups for the variables under study. SOC presented average values ​​of nr = 0.04%, Ag = 0.08% and Ce = 0.13%; average SOM was estimated as nr = 0.07%; Ag = 0.15% and Ce = 0.23%. Ce is recognized as presenting the greatest forest potentiality by stocking capacity 2.73 Mg C ha-1 to the soil.